Characteristic Anopheles sp Larvae Breeding Places in theVillageWay Muli Lampung South - Pangastuti, Rayi Lujeng; Kurniawan, Betta; Rosa, Emantis (Majority, 2015)
ABSTRACT Malaria is a disease transmitted by several factors, namely parasites/plasmodium (agent), human factors (host), Anopheles sp mosquito (vector) and the environment (environment). The purpose of this study was to investigate the characteristics of larvae breeding places of Anopheles sp. The research was conducted in October - November 2014 in the village of Way Muli, District Rajabasa, South Lampung. Observation station 1 in the form of pool shrimp (hatchery), observation station 2 is gutter, 3 observation station grouper hatchery ponds, pools abandoned station 4 hatchery waste disposal and observation station 5 is the estuary. Results of research on mosquito breeding places is the depth range between 40,2 to 12 cm, the temperature 30,1 to 32 °C, salinity 10,3 to 29 ‰, pH 7,33 to 933; and DO 4,29 to 9,52 mg/L. Water plant breeding places of mosquitoes algae type Oscillatoria sp class (cyanophyta), Melosira varians class (Bacillariophyta), Melosira nummuloides class (Bacillariophyta), Spirogyra sp class (Chlorophyta), Enteromorpha intestinalis class (Chlorophyta), Cladophora fracta class (Chlorophyta). Aquatic animals in the hatchery Aplocheilus panchax (fish head tin), Gerris sp (anggang–anggang), Palaemonetes sp (shrimp), Culex sp, the gutter found Aplocheilus pancha (Fish head tin), Culex sp, the estuary was found Gerris sp (anggang-anggang), Palaemonetes sp (shrimp), whereas the grouper hatchery ponds and pond hatchery waste disposal of abandoned animals not found water. The highest density of larvae found in the observation station at the mouth (22,08 / 250 ml), the lowest in the hatchery (64,67 / 250ml). Key words: Larvae density, breeding places, malaria vectors, way muli ABSTRAK Malaria adalah penyakit yang ditularkan oleh beberapa faktor, yaitu parasit/plasmodium (agent), faktor manusia (host), nyamuk Anopheles sp (vektor) dan lingkungan (environment). Tujuan Penelitian ini untuk mengetahui karakteristik tempat perindukan larva nyamuk Anopheles sp. Penelitian ini dilaksanakan pada bulan Oktober – November 2014 di Desa way Muli, Kecamatan Rajabasa, Kabupaten Lampung Selatan. Stasiun pengamatan 1 berupa Kolam pembenihan udang (hatchery), stasiun pengamatan 2 adalah selokan, stasiun pengamatan 3 kolam pembenihan ikan kerapu, stasiun 4 kolam terlantar pembuangan limbah hatchery dan stasiun pengamatan 5 adalah muara. Hasil penelitian pada tempat perindukan nyamuk adalah kedalaman berkisar antara 40,2 - 12 cm, suhu 30,1 - 32 °C, salinitas 10,3 - 29 ‰, pH 7,33 - 9,33, dan DO 4,29 – 9,52 mg/L. Tumbuhan air disekitar tempat perindukan nyamuk ditemukan alga jenis Oscillatoria sp kelas (cyanophyta), Melosira varians kelas (Bacillariophyta), Melosira nummuloides kelas (Bacillariophyta), Spirogyra sp kelas (Chlorophyta), Enteromorpha intestinalis kelas (Chlorophyta), Cladophora fracta kelas (Chlorophyta). Hewan air pada hatchery Aplocheilus panchax (ikan kepala timah), Gerris sp (anggang-anggang), Palaemonetes sp (udang), Culex sp, pada selokan ditemuakan Aplocheilus panchax (ikan kepala timah), Culex sp, pada muara ditemukan Gerris sp (anggang-anggang), Palaemonetes sp (udang), sedangkan pada kolam pembenihan ikan kerapu dan kolam terlantar pembuangan limbah hatchery tidak ditemukan hewan air. Kepadatan larva tertinggi ditemukan pada stasiun pengamatan di muara (22,08 ekor/250 ml) terendah pada hatchery (64,67 ekor/250ml). Kata Kunci : Kepadatan larva, tempat perindukan, vektor malaria, way muli